Childhood Allergies: The Role of Maternal Depression and Anxiety, and Family Strain - Ming Wai Wan; Molly Janta-Lipinski; Cemre Su Osam (MDPI AG, 2021)
Maternal mental disorder and a negative family emotional climate are a great source of stress for many children, yet their role in the childhood development or expression of asthma and allergies remains poorly understood, particularly beyond the first 1-2 years of life. The current study tested whether childhood allergy onset and symptomatology would be predicted by (1) perinatal and any time exposure to maternal depression or anxiety and (2) current family emotional strain (whole family, mother-child). UK mothers of children aged 2-12 years (N = 328) living with them completed an online survey of measures. Children exposed to maternal depression were almost twice as likely to be diagnosed and almost five times as likely to screen positive for an allergic disorder. Perinatal depression was linked to childhood allergies, but more moderately. Any anxiety exposure, and not specific to the perinatal period, predicted allergy status. Family emotional strain contributed independently to variance in concurrent child allergic symptomatology. All results were independent of potential confounders and current mental distress. The findings highlight the importance of maternal mental health and family function in the child's neuro-immune development, and that these factors need to be addressed in the treatment of childhood allergic disorders.